Electron beam formation and its effect in novel plasma-optical device for evaporation of micro-droplets in cathode arc plasma coating - Goncharov, A.A.; Maslov, V.I.; Naiko, L.V. (Вопросы атомной науки и техники, 2016)
The additional pumping of energy into arc plasma flow by the self-consistently formed radially directed beam of
high-energy electrons for evaporation of micro-droplets is considered. The radial beam appears near the inner
cylindrical surface by secondary ion - electron emission at this surface bombardment by peripheral arc plasma flow
ions. The beam is accelerated by electric potential jump, appeared in a cylindrical channel of the plasma-optical
system in crossed radial electrical and longitudinal magnetic fields. The high-energy electrons pump, during the time
of micro-droplet movement through the system, the energy, which is sufficient for evaporation of micro-droplets. Рассматривается дополнительная накачка энергии в поток дуговой плазмы с помощью
самосогласованно образуемого радиального пучка электронов для испарения капель. Пучок появляется
вблизи внутренней цилиндрической поверхности за счёт вторичной ионно-электронной эмиссии при её
бомбардировке периферийными ионами потока. Пучок ускоряется скачком электрического потенциала,
который появляется в цилиндрическом канале плазмо-оптической системы в скрещенных полях.
Высокоэнергетичные электроны накачивают за время движения микрокапель через систему энергию,
которая достаточна для испарения микрокапель. Розглядається додаткове накачування енергії в потік дугової плазми за допомогою самоузгоджене
утвореного радіального пучка електронів для випаровування крапель. Пучок з'являється поблизу
внутрішньої циліндричної поверхні за рахунок вторинної іонно-електронної емісії при її бомбардуванні
периферійними іонами потоку. Пучок прискорюється стрибком електричного потенціалу, який
з'являється в циліндричному каналі плазмооптичної системи в схрещених полях. Високоенергетичні
електрони накачують за час руху крапель через систему енергію, яка достатня для випаровування
крапель.